Eksplorasi Etnomatematika pada Kirab Tumpeng di Desa Biting Kecamatan Arjasa - Wulandari, Syarifah; Lutfiyah; Hidayatin, Nur (FKIP Universitas Mataram, 2025)
This study explores the ethnomathematic elements found in the Tumpeng Parade in Biting Village, Arjasa District. The Tumpeng Parade is part of the community's culture that contains mathematical concepts, such as geometry, patterns, symmetry, and the concept of numbers in the arrangement and presentation of tumpeng. The main objective of this study is to examine how local communities apply mathematical principles passed down through generations in the creation and organization of the Tumpeng Parade. Specifically, the aim of this study is to understand the relationship between culture and mathematics in everyday life. Data for this study were collected through documentation, interviews, and observations using a qualitative descriptive research methodology. The findings of this study are expected to provide an understanding of the mathematical concepts of the Tumpeng Parade and can be used as a contextual learning medium for the younger generation.